Influence of Psychiatric Disorders on Recovery and Prognosis from Gynecological Surgery (Global Journal of Medical Research, 2023)
Introduction The influence of psychiatric disorders on the recovery and prognosis of Gynecological surgery is a topic of clinical and scientific relevance Patients with disorders psychiatric conditions such as depression anxiety and post-traumatic stress disorder can present additional challenges during the perioperative period understand how these disorders affect the results of gynecological surgery is essential for a holistic and personalized approach to the care of these patients Purpose The purpose of this study was to investigate the influence of psychiatric disorders on the recovery and prognosis of gynecological surgery analyzing the relationship between these disorders and complications postoperative conditions long-term results and quality of life of patients Methodology A systematic review was carried out according to the PRISMA checklist Preferred Reporting Items for Systematic Reviews and Meta-Analyses The search comprehensive survey was conducted on major medical databases including PubMed Embase and Scopus using the following MeSH terms Medical Subject Headings and their combinations psychiatric disorders gynecological surgery recovery postoperative prognosis and quality of life Published studies were included over the last 10 years with relevant data on the influence of psychiatric disorders in gynecological surgery